The influence of product innovation and digital marketing strategies in driving increased sales of Jo Fried Chicken in Medan Amplas District - Atika Aini Nasution; Zahara, Meutia; Pikri Wahyu Amri (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The purpose of this study is to find out what appropriate marketing strategies are implemented by Jo Fried Chicken UMKM in an effort to increase their sales volume and to find out the creative product innovations implemented by Jo Fried Chicken UMKM. Materials and methods. The research method in this thesis is multiple regression analysis. The independent variables in this study are Product Innovation and Digital Marketing Strategy while the dependent variable is Sales Increase. The research population in this study is consumers at Jo Fried Chicken, using a purposive sampling method and using the Slovin formula obtained 80 respondents. The type of data used is primary data. The results of this study prove that product innovation has a significant effect on increasing sales statistically because the t_count value is 9.184, with a t_table value of 1.990, note that the t_count value (9.184)> t_table (1.990) with a probability or sig. of the product innovation variable is 0.000 <0.05. Digital marketing does not have a significant effect on increasing sales statistically because the t_count value is 0.606, with a t_table value of 1.990, note that the t_count value (0.606) <t_table (1.990) with a probability or sig. of the digital marketing variable is 0.546> 0.05. Conclusion. Product innovation has a significant effect on sales growth statistically. Digital marketing has no significant effect on sales growth statistically. Product innovation and digital marketing strategy simultaneously have a significant effect on sales growth.